Role of deep eutectic solvents as pretreatment medium for biomass transformation - Chung Loong, Yiin; Kok Liang, Yap; Dayang Salyani, Abang Mahmod; Bridgid Lai Fui, Chin; Serene Sow Mun, Lock; Yi Herng, Chan; Kin Wai, Cheah; Martin J., Taylor; Georgios, Kyriakoug (Elsevier Inc, 2022)
Traditionally, biomass utilization was realized through the concept of biorefineries and the purpose of using biomass was mostly energy-driven. Over the years, the concept of biomass valorization shifted its focus toward unleashing the maximum potential of biomass in downstream processing such as for the production of various energy carriers and value-added bioproducts or chemicals. The main stepping stone toward realizing biomass transformation can be attributed to the ubiquitous nature of biomass, from which most of the biopolymers exhibited high recalcitrance in common solvents due to the heterogeneous polyphenolic structure of the lignin and the highly ordered cellulose’s crystalline structure. The recalcitrance of biomass poses constraints in the biomass-to-biofuels conversion or other valueadded bioproducts which typically involves three major steps: pretreatment, hydrolysis, and fermentation (Binod & Pandey, 2015). The pretreatment of biomass can be regarded as the most important step in biomass processing. In this sense, the goal of biomass pretreatment is to disintegrate the lignin barrier and make the celluloses, hemicelluloses, and other substrates accessible, as well as to enable the further processing and recovery of the valuable components embedded within the biomass.